Polikotomi Pilihan Pengembangan Ekowisata Kawasan Borobudur - Soeroso, Amiluhur (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2010)
Aim of the study is assessing consumer behavior of tourist who visits to Borobudur if an ecotourismÃ‚Â concept will be used in this area. Data were obtained from participation of tourists in BorobudurÃ‚Â temple and surrounding area of Jogjakarta municipality. Then, it was used polychotomous choiceÃ‚Â framework for finishing it.The results indicate that ecotourism concept able to properly apply. Then, education and incomeÃ‚Â are becoming vehicle decision public policy for managing Borobudur area. Consumer knowledgeÃ‚Â about living environment more and more higher so that their activity choice is in green tourismÃ‚Â products. Ã‚Â Consequently, Ã‚Â the survival Ã‚Â of Ã‚Â Borobudur Ã‚Â world Ã‚Â heritage Ã‚Â site Ã‚Â in Ã‚Â the Ã‚Â future Ã‚Â will Ã‚Â fullyÃ‚Â depend on its sustainable development policy.